The effects of individual-level smoking cessation interventions by socioeconomic groups and their potential impact on inequalities in smoking - Theodoulou, A; Fanshawe, T; Leavens, E; Theodoulou, E; Wu, A; Heath, L; Stewart, C; Nollen, N; Ahluwalia, J; Butler, A; Hajizadeh, A; Thomas, J; et al. (University of Oxford, 2024)
Supplementary information (table and figure) in Microsoft Excel that provide additional information to accompany the Cochrane review: The effects of individual-level smoking cessation interventions by socioeconomic groups and their potential impact on inequalities in smoking